Codex Nicholsonianus. (November 2021) - Woudhuysen, George
Abstract : Frankness is not a quality one naturally associates with Themistius, that most sinuous of the fourth century's official spokesmen, but the opening of his first speech ('On the Love of Mankind') is disarmingly frank. Invited to address Constantius II at Ancyra in the spring of 342, the young orator had an unusually difficult brief: violent riots in Constantinople had recently seen Hermogenes (a senior general) killed by a mob, relations with Constans (emperor in the west) were tense and war with Persia was rumbling away on the eastern frontier. The situation surely called for cliché — the familiar refuge of the panegyrist in a tight spot — but Themistius responded with a rather daring candour. Not for him some faltering introduction of the various themes set out in the rhetorical handbooks. Instead, he opened by offering his listeners an expert's guide to the tropes of conventional panegyric: those familiar descriptions of magnificent armies, glittering imperial adornment and the emperor's physical vigour ( Or . 1.2a–b) to which his courtly audience must have been almost numb. With these curtly dismissed as so much hackwork, he delivered a boldly original oration: a philosophical treatment of the emperor's inner virtue. It is quite a performance. One can see why so many and such different emperors found themselves in need of Themistius' eloquence.